P011 New insights into the pathogenic potential and signalling network of NKG2D+ CD4+ T-cells in Crohn's Disease. (21st January 2022) - Modos, D; Gul, L; Lo, J; Madgwick, M; Cozzetto, D; Lord, G; Korcsmaros, T; Powell, N
Abstract: Background: A subset of mucosal CD4 + T-cells expressing the NK cell receptor NKG2D (encoded by the KLRK1 gene) are enriched in patients with Crohn's Disease (CD). In pre-clinical models of colitis, NKG2D expression was confined to a subset of colonic CD4+ T-cells that hyper-expressed interferon gamma. However, the functional role of these cells in mediating intestinal inflammation is unknown. Little is known about the transcriptional regulation of this population or the key signalling networks that they engage. Methods: Pre-clinical models of CD, adoptive transfer experiments and in vitro culture systems were used to investigate the phenotype and pathogenicity of NKG2D using Klrk1 -/- and WT mice. Signalling networks and interactions between NKG2D, key transcription factors and relevant cytokines were investigated by probing published single-cell RNA seq data (Martin et al. Cell 2019). Pathway members of potential interactions were collected from the literature, and the OmniPath database and we applied a heat propagation model. Results: NKG2D-expressing T-cells were potently pathogenic when adoptively transferred to Rag1 - mice, mediating more severe disease than Klrk1 -/- CD4 + T-cells. Notably, Klrk -/- T-cells were still able to induce colitis, indicating that NKG2D-independent pathogenic pathways also exist. Chromatin immunoprecipitation demonstrated that T-bet bound at the transcriptional start site of the Klrk1 locus in WT Th1 cells, but not Tbx21 -/- Th1 T-cells. There were significantly fewer NKG2D expressing CD4 + T-cells from Tbx21 -/- mice, and forced expression of T-bet in Tbx21 -/- Ifng -/- double knockout CD4 + T-cells induced Klrk1 mRNA expression, consistent with T-bet being a transcriptional activator of the Klrk1 gene. The NKG2D model network reached FOS, NFKB and JUN transcription factors depending on the presence of the NKG2D. The model distinguished two comparable pathway activation - one with active PRKCA in T-cells including CD8 + T-cells and one with less active PRKCA mostly in macrophages. Comparing the inflamed and uninflamed conditions, highly activated T-cells, and a population of Th17 + TRM cells had an active KLRK pathway only in inflamed Crohn disease. Conclusion: NKG2D expressing colonic CD4 + T-cells are potent cytokine producing cells and are more colitigenic than their NKG2D-negative counterparts. Network-based heat propagation showed that specific populations of colonic memory T cells are active only in the inflamed condition, meanwhile, the model identified two types of cells that had active KLRK1 pathway: one which was PRKCA dependent activity and one which had non-PRKCA dependent activity. We also identify T-bet as an important transcriptional regulator of NKG2D expression.